2010
DOI: 10.2164/jandrol.109.007583
|View full text |Cite
|
Sign up to set email alerts
|

Seminal Plasma Proteins as Potential Markers of Relative Fertility in Boars

Abstract: This study investigated whether specific proteins from distinct seminal plasma fractions of boars could be related to in vivo fertility. Nine boars with acceptable sperm motility and morphology for use in artificial insemination demonstrated major differences in total number born and pregnancy rate when low sperm doses (1.5 billion sperm) were used to breed a minimum of 50 gilts per boar. The 2 lowest-fertility and 2 highest-fertility boars were chosen for evaluation of specific seminal plasma proteins. On 4 o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
82
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(92 citation statements)
references
References 51 publications
3
82
1
Order By: Relevance
“…This handling is now switching towards a growing interest to scrutinize SP-composition and evaluate its relevance for sperm functionality, even fertility. Recent findings support the complex composition of boar SP [50][51][52] and also demonstrate the relevance of some SP-components, such as Glutathione Peroxidase 5 [53] or Paraoxonase-I [54], for promoting sperm fertility of liquid stored semen IA-doses.…”
Section: Seminal Plasma a Mine To Fully Discoversupporting
confidence: 60%
See 1 more Smart Citation
“…This handling is now switching towards a growing interest to scrutinize SP-composition and evaluate its relevance for sperm functionality, even fertility. Recent findings support the complex composition of boar SP [50][51][52] and also demonstrate the relevance of some SP-components, such as Glutathione Peroxidase 5 [53] or Paraoxonase-I [54], for promoting sperm fertility of liquid stored semen IA-doses.…”
Section: Seminal Plasma a Mine To Fully Discoversupporting
confidence: 60%
“…In contrast, other SP-components, such as the major proteins PSP-1 and AQN-3, could impair fertility of boar sperm [53,55]. This functional contrast between SP-components should be considered before using raw SP as sperm extender of post-thaw semen, action leading to inconsistent fertility results [56,57].…”
Section: Seminal Plasma a Mine To Fully Discovermentioning
confidence: 99%
“…The 55-kDa fertility-associated protein has been identified as osteopontin (Cancel et al 1999), and the 26-kDa fertility-associated protein has been identified as lipocalintype prostaglandin D synthase (Gerena et al 1998). Using the Western blotting technique, Novak et al (2010) identified porcine seminal proteins, namely AWN-1 with molecular weight of 14 kDa and osteopontin with molecular weight of 70 kDa (OPN-70), 12 kDa (OPN-12) and 9 kDa (OPN-9). In pig, the addition of osteopontin during in vitro fertilization reduced polyspermy rates (Hao et al 2006) and improved embryo development after fertilization.…”
Section: Resultsmentioning
confidence: 99%
“…Inter-animal differences in their ability to sustain sperm cryopreservation had been associated to the SP-composition (Flowers, 2001;Novak et al, 2010), genetic factors (Thurston et al, 2002), or by the existence of distinct spermatozoa subpopulations in the ejaculate, in terms of their morphological characteristics (Thurston et al, 2001) or movement patterns (Cremades et al, 2005).…”
mentioning
confidence: 99%